Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $X$ is a real Reflexive Banach space. Let $A:X\rightarrow X^{\star}$ be a Pseudo Monotone operator, i.e. if $u_{n}\rightharpoonup u$ and $\limsup\langle Au_{n},u_{n}-u\rangle\leq 0$, then $$\langle Au,u-w\rangle\leq\liminf\langle Au_{n},u_{n}-w\rangle,\ \forall\ w\in X$$

where $\rightharpoonup$ stands for weak convergence and $\langle\ \rangle$ represents duality.

I want to prove that $$Au_{n}\rightharpoonup Au$$ and $$\langle Au_{n},u_{n}\rangle\rightarrow \langle Au,u\rangle$$

What i have tried?

We can write $\langle Au_{n},u_{n}\rangle=\langle Au_{n}-Au,u_{n}-u\rangle-\langle Au,u\rangle+\langle Au_{n},u\rangle+\langle Au,u_{n}\rangle$.

I showed that $\langle Au_{n}-Au,u_{n}-u\rangle\rightarrow 0$. Then if i can show that $Au_{n}\rightharpoonup Au$, the problem is solved because $X$ is reflexive (so $\langle Au_{n},u\rangle\rightarrow\langle Au,u\rangle$).

Any idea? Thanks

share|cite|improve this question
up vote 1 down vote accepted

1 - $\lim\langle Au_n,u_n-u\rangle=0$

Indeed, ofr $w=u$ we have

\begin{eqnarray} 0 &\leq& \liminf\langle Au_n,u_n-u\rangle \nonumber \\ &\leq& \limsup\langle Au_n,u_n-u\rangle \nonumber \\ &\le& 0 \end{eqnarray}

Therefore, $\lim\langle Au_n,u_n-u\rangle=0$

2 - $\langle Au,u-w\rangle\leq\liminf\langle Au_n,u-w\rangle,\ \forall\ w\in X$

We have, (im using 1 here)

\begin{eqnarray} \langle Au,u-w\rangle &\leq& \liminf\langle Au_n,u_n-w\rangle+\liminf\langle Au_n,-u_n+u\rangle \nonumber \\ &\leq& \liminf\langle Au_n,u_n-u_n+u-w\rangle \nonumber \\ &=& \liminf\langle Au_n,u-w\rangle \end{eqnarray}

3 - $\langle Au_n,v\rangle\rightarrow\langle Au,v\rangle,\ \forall\ v\in X$

Take $w=u-v$ in 2. Hence

\begin{eqnarray} \langle Au,v\rangle &\leq& \liminf\langle Au_n,v\rangle \nonumber \\ &\leq& \limsup\langle Au_n,u_n-u_n+u-u+v\rangle \nonumber \\ &\le& \limsup\langle Au_n,u_n-u\rangle+\limsup\langle Au_n,-u_n+u+v\rangle \\ &=& \limsup-\langle Au_n,u_n-(u+v)\rangle \\ &=& -\liminf\langle Au_n,u_n-(u+v)\rangle \\ &\leq& -\langle Au,u-(u+v)\rangle \\ &=& \langle Au,v\rangle \end{eqnarray}

Because $X$ is reflexive, by using 3 we get that $Au_n\rightharpoonup Au$

4 - $\lim\langle Au_n-Au,u_n-u\rangle\rightarrow 0$

By using the hypothesis with $w=u$ we have that

\begin{eqnarray} 0 &\leq& \liminf\langle Au_n,u_n-u\rangle \nonumber \\ &=& \liminf\langle Au_n,u_n-u\rangle+\liminf\langle Au,u_n-u\rangle \nonumber \\ &\le& \liminf\langle Au_n-Au,u_n-u\rangle \\ &\leq& \limsup\langle Au_n-Au,u_n-u\rangle \\ &\leq& \limsup\langle Au_n,u_n-u\rangle \\ &\leq& 0 \end{eqnarray}

5 - $\langle Au_n,u_n\rangle\rightarrow\langle Au,u\rangle$

Note that $$\langle Au_n,u_n\rangle=\langle Au_n-Au,u_n-u\rangle-\langle Au,u\rangle+\langle Au_n,u\rangle+\langle Au,u_n\rangle$$

It follows from 3,5 and $u_n\rightharpoonup u$ that $$\lim\langle Au_n,u_n\rangle=\langle Au,u\rangle$$

Please verify if my proof is correct.

Id like to observe that the converse of this theorem is also true and much more easy to prove.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.